2022
DOI: 10.3389/fpsyg.2022.881269
|View full text |Cite
|
Sign up to set email alerts
|

Context matters during pick-and-place in VR: Impact on search and transport phases

Abstract: When considering external assistive systems for people with motor impairments, gaze has been shown to be a powerful tool as it is anticipatory to motor actions and is promising for understanding intentions of an individual even before the action. Up until now, the vast majority of studies investigating the coordinated eye and hand movement in a grasping task focused on single objects manipulation without placing them in a meaningful scene. Very little is known about the impact of the scene context on how we ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This did not occur consistently across stimulus locations, suggesting that salience even when relevant to the task is not the key predictor of gaze direction when active exploration is occurring around a scene with strong spatial layout cues. In studies with more natural environments, other factors like memory 18 and scene context 27 , 28 have been shown to influence searching for objects in a simulated real world context in virtual reality. Other research has also suggested that encoding of stimulus salience and its utility in driving gaze behaviour in a naturalistic scene is time limited and diminishes throughout a trial 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This did not occur consistently across stimulus locations, suggesting that salience even when relevant to the task is not the key predictor of gaze direction when active exploration is occurring around a scene with strong spatial layout cues. In studies with more natural environments, other factors like memory 18 and scene context 27 , 28 have been shown to influence searching for objects in a simulated real world context in virtual reality. Other research has also suggested that encoding of stimulus salience and its utility in driving gaze behaviour in a naturalistic scene is time limited and diminishes throughout a trial 29 31 .…”
Section: Discussionmentioning
confidence: 99%